The Impact of Assisted Sprinting Training (As) and Resisted Sprinting Training (Rs) in Repetition Method on Improving Sprint Acceleration Capabilities - Ricky Wibowo; Dikdik Zafar Sidik; Yudy Hendrayana (Universitas Pendidikan Indonesia, 2017)
The purpose of this research is to determine the impact of assisted sprinting training (AS) and resisted sprinting training (RS) in repetition method on improving sprint acceleration capabilities. This research used experimental method in pre-test and post-test design. The research sample were twelve male collegiates track sprinters, athletic division Indonesia University of Education, Bandung. Six male collegiates track sprinters for AS and six male collegiates track sprinters for RS. It used simple random sampling. The instrument used is 30 m sprint test. After training three times per week for six week, data were obtained from pre-test and post-test processed statistically by t-test. The AS group and RS group showed significant changes on improving sprint acceleration capabilities. No significant different between AS and RS on improving sprint acceleration capabilities. In AS the increase is better than RS at a distance of 10 m from a distance of 30 m. While, in RS the increase is better than AS at a distance of 10-20 m and 20-30 m from a distance of 30 m. Accordingly, to improve acceleration at a distance 10 m use AS, while to improve acceleration at a distance of 10-20 m and 20-30 m from a distance of 30 m use RS.